Closure of oro‐antral fistulae in conjunction with functional endoscopic sinus surgery: A systematic review and retrospective analysis. (10th March 2022) - Aruede, Glenda; Smart, Keith; Mustafa, Shakir
Abstract: Aim: An oro‐antral communication (OAC) is a recognised potential complication of maxillary tooth extraction. If it does not resolve, a pathological epithelialised tract or oro‐antral fistula (OAF) can develop. The aim of this systematic review was to determine whether OAF closure with functional endoscopic sinus surgery (FESS) provides an effective approach for total closure and relief of sinusitis. Material and Methods: The systematic review followed the PRISMA format. An electronic database search was performed to identify publications in English between 2010 and 2020, containing human subjects with radiographic evidence of sinus pathology, relating to OAF formation following extraction, and simultaneous OAF closure with FESS. Success was measured as total closure and relief of symptoms after 3 weeks. A retrospective analysis of patients within the Cwm Taf Morgannwg University Health Board that fit the eligibility criteria over a 5‐year period was conducted and compared with the results of the review. Results: Five papers were included in the review, covering 86 OAFs, with an overall success rate of 97.7% (84/86). Two patients required revision surgery, due to recurrent OAFs, who were both diabetic and smokers. A total of 13 patients met the case series' inclusion criteria, and 100% success was achieved. A minor complication of post‐operative nasal synechia arose in 4/99 (4.0%) patients. Evidence‐based guidance was created for local dentists encountering an acute OAC. Conclusions: OAF closure with FESS can be considered a highly effective approach, leaving patients symptom‐free. It is important that protocols are in place for dentists suspecting an OAC to expedite patient management.